2010
DOI: 10.1097/cej.0b013e328338f7d2
|View full text |Cite
|
Sign up to set email alerts
|

The role of oestrogen in the pathogenesis of obesity, type 2 diabetes, breast cancer and prostate disease

Abstract: A detailed review of the literature was performed in a bid to identify the presence of a common link between specific hormone interactions and the increasing prevalence of global disease. The synergistic action of unopposed oestrogen and leptin, compounded by increasing insulin, cortisol and xeno-oestrogen exposure directly initiate, promote and exacerbate obesity, type 2 diabetes, uterine overgrowth, prostatic enlargement, prostate cancer and breast cancer. Furthermore these hormones significantly contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 165 publications
(227 reference statements)
1
32
0
Order By: Relevance
“…The development of healthy mammary glands requires estrogen activation of ERs that triggers specific signaling pathways responsible for mammary cell proliferation and differentiation. Nevertheless, altered ER signaling is implicated in the abnormal cell proliferation as well as the development and progression of breast cancer [5, 6]. Especially, the activation of ER-α is believed to promote the growth of breast tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The development of healthy mammary glands requires estrogen activation of ERs that triggers specific signaling pathways responsible for mammary cell proliferation and differentiation. Nevertheless, altered ER signaling is implicated in the abnormal cell proliferation as well as the development and progression of breast cancer [5, 6]. Especially, the activation of ER-α is believed to promote the growth of breast tumors.…”
Section: Introductionmentioning
confidence: 99%
“…If NSAIDs do in fact modulate hormone levels, this could have a large public health impact due to the common use of NSAIDs and the high prevalence of potentially hormone-related diseases such as type 2 diabetes, 6 cardiovascular disease, 8 and prostate cancer. 5,33,34 * Estimates inversely weighted to the probability of selection; percents shown are column percents and may not sum to 100 due to rounding † Use of prescription (Rx) NSAIDs with or without over-the-counter (OTC) NSAIDs ‡ Defined as a history of coronary artery bypass, angioplasty, myocardial infarction, angina, arrhythmia requiring a pacemaker, heart rhythm disturbance, congestive heart failure, transient ischemic attack, stroke, carotid artery surgery, intermittent claudication, surgery or angioplasty for arterial disease of the leg, pulmonary embolism, aortic aneurysm, deep vein thrombosis, Raynaud's disease, or peripheral vascular disease Table 2 Adjusted geometric mean hormone levels by non-steroidal anti-inflammatory drug ( Clin Endocrinol (Oxf). Author manuscript; available in PMC 2013 February 1.…”
Section: Such Measurement Error Likely Resulted In An Underestimate Omentioning
confidence: 99%
“…Montgomery et al (2010) have suggested that hormones such as oestrogen could influence hearing ability through action on inner-ear oestrogen receptors (Stenberg et al 2001). Obesity has been associated with the unopposed action of endogenous oestrogens (Williams 2010;Hulcrantz 2006). There is also evidence for menstrual fluctuations in auditory perception (Haggard and Gaston 1978) that could point to a hormonal effect on hearing ability.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%